Music and spirituality: Reflections on the role of music and the natural environment in healing - Bist, Dinesh (Journal for the Study of Spirituality, 2021)
This article focuses on our personal experiences of the role of music and nature in healing. We explore ancient texts and more recent research in the area of music, neuromusicology and spirituality and correlate these with our experiences. One of us has suffered severe trauma in the form of a spinal cord injury; the other has experienced deep-vein thrombosis. We both present reflexive accounts which demonstrate how music played a part in the healing process; one of us also links this to the impact of the natural environment. We hope that others can benefit from the lessons we have learned from our experiences.